Long-term outcome of bisphosphonate therapy in paediatric CNO: a single-centre cohort study - Sarah Remtoula; Federica Anselmi; Justin Ulm; Linda Rossi-Semerano; Caroline Galeotti; Sandrine Chilloh; Vanessa Lapierre; Ines Mannes; Marie Robert; Perrine Dusser (Pediatric Rheumatology, 2026)
Abstract Objectives Chronic non-bacterial osteomyelitis (CNO) is a rare autoinflammatory bone disorder affecting mainly children. While non-steroidal anti-inflammatory drugs (NSAIDs) are the first-line therapy, bisphosphonates (BPs) are frequently used in refractory cases despite limited evidence. This study evaluated the clinical, laboratory, and radiological outcomes of BPs therapy in children affected by CNO. Methods We conducted a single-centre retrospective study of 30 children with CNO treated with intravenous BPs between 2010 and 2023. Data were collected at diagnosis, 12 months after BPs initiation (T2), and at last follow-up (T3). Multivariate analyses were performed to identify factors associated with treatment outcomes. Results At baseline, 80% of patients reported inflammatory pain and 30% had vertebral fractures. Clinical remission was achieved in 46.7% of patients at T2 and in 66.7% at final follow-up. Pain severity and inflammatory markers improved significantly over time. No new vertebral fractures or worsening of vertebral lesions were observed during follow-up, and vertebral bone marrow oedema resolved in all patients with vertebral involvement. MRI abnormalities frequently persisted despite clinical remission. A higher number of BP courses was associated with improved clinical and laboratory outcomes, whereas no clear additional radiological benefit was observed beyond four courses. BPs were generally well tolerated. Conclusion BPs are effective for symptom control in children affected by CNO and may be particularly beneficial in vertebral disease. Persistent MRI abnormalities despite clinical remission highlight the complexity of treatment targets in CNO. Prospective studies are needed to optimize treatment duration and clarify the long-term impact of BP therapy.